HUBUNGAN KEPATUHAN PELAKSANAAN PENCEGAHAN DAN PENGENDALIAN INFEKSI DENGAN KEJADIAN COVID-19 PADA PERAWAT DI INSTALASI RAWAT INAP RSU KAB. TANGERANG - Winda Sugiyanti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Background: Based on the data that has been issued by the WHO on June 10, 2020 a globally confirmed Covid-19 virus as many as 7,221,717 people and in Indonesia as many as 34,316 people. In Banten positive case Covid-19 as many as 1,096 people and 10 cases have been cured. Objective: To know the relationship of compliance prevention and control of infection with the incidence of Covid-19 on the nurse in the inpatient installation General Hospital of Tangerang Regency. Method: This study uses the analytical descriptive design with a Cross sectional approach, with a sample number of 110 respondents using the purposive sampling technique, the instrument used is a questionnaire. Research results: Statistical test results with the Chi square test using the results of Fisher's Exact Test obtained p value = 0.011 < 0.05 then it can be declared Ho rejected Ha is accepted meaning that there is a significant link between compliance prevention and control of infection with the incidence of Covid-19 on the nurse in inpatient installation RSU District Tangerang. From the results of analysis obtained also the value of OR = 0,051, meaning that the nurse who complies with the possibility of transmission of Covid-19 will be low of 0.051 compared to disobedient nurses.